Dynamic Li+ Capture through Ligand‐Chain Interaction for the Regeneration of Depleted LiFePO4 Cathode - Zhao, Xin‐Xin; Wang, Xiao‐Tong; Guo, Jin‐Zhi; Gu, Zhen‐Yi; Cao, Jun‐Ming; Yang, Jia‐Lin; Lu, Feng‐Qi; Zhang, Jing‐Ping; Wu, Xing‐Long (Advanced materials (Weinheim), 2024)
After application in electric vehicles, spent LiFePO4 (LFP) batteries are typically decommissioned. Traditional recycling methods face economic and environmental constraints. Therefore, direct regeneration has emerged as a promising alternative. However, irreversible phase changes can significantly hinder the efficiency of the regeneration process owing to structural degradation. Moreover, improper storage and treatment practices can lead to metamorphism, further complicating the regeneration process. In this study, a sustainable recovery method is proposed for the electrochemical repair of LFP batteries. A ligand‐chain Zn‐complex (ZnDEA) is utilized as a structural regulator, with its ─NH─ group alternatingly facilitating the binding of preferential transition metal ions (Fe3+ during charging and Zn2+ during discharging). This dynamic coordination ability helps to modulate volume changes within the recovered LFP framework. Consequently, the recovered LFP framework can store more Li‐ions, enhance phase transition reversibility between LFP and FePO4 (FP), modify the initial Coulombic efficiency, and reduce polarization voltage differences. The recovered LFP cells exhibit excellent capacity retention of 96.30% after 1500 cycles at 2 C. The ligand chain repair mechanism promotes structural evolution to facilitate ion migration, providing valuable insights into the targeted ion compensation for environmentally friendly recycling in practical applications. The introduction of the ligand chain within the Zn complex dynamically modulates the variational structure, enlarging the main framework of LFP and expediting the de‐intercalation of Li+. This process revitalizes the composition, structure, and electrochemical performance of LFP, restoring them to levels comparable to that of newly produced LFP even under severe degradation conditions during the operation of regenerated batteries.